USING DIFFERENT METHODS TO TRANSLATE ENGLISH TEXTS - Suvonova Diyora Baxodir qizi (Ta'lim innovatsiyasi va integratsiyasi, 2023)
Abstract: At present, one of the most essential problems among students who are learning English as their second language is to translate English texts into their mother language. The objectives of this article are to point out main errors and challenges that students are facing during translation and give an explanation of effective methods in translating English texts. In this article descriptive quantitative method is used. There are five types of translating methods that can be understandable for students are explained. It can be seen that most students are unable to translate English text because of their vocabulary range and lack of strategies in translating. Article was concluded with the opinion that it requires an ability to understand which method to use in translating in order to achieve faultless translating, therefore students need to be aware of methods of translating that will be mentioned below.